2006
DOI: 10.1007/s00701-006-1068-y
|View full text |Cite
|
Sign up to set email alerts
|

20 years follow-up after the first microsurgical lumbar discectomies in Iceland

Abstract: Outcome was very good with 92.0% return to work and 91.1% patient satisfaction. The recurrence rate was 12.7% with a substantial number of cases occurring 10-20 years after operation. To conclude, microsurgical discectomies maintain a high success rate in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Indeed, clinical studies have established that there is an unclear relationship between radiological signs of LDH and degree of sciatica or other clinical symptoms 15 . In keeping with the main indication for LDHsurg 13 20 ; the neuropathic and painful symptoms of sciatica, we find of interest that height is inversely correlated with peripheral nerve conduction velocity 42 and has been shown to increase risk of peripheral sensory neuropathy in diabetes 43 , peripheral insensate neuropathy 44 , HIV neuropathy 45 and post-mastectomy neuropathic pain syndrome 46 . While the pathogenesis behind the relationship between height and neuropathic pain is unclear, increased height in humans is known to associate with increased axonal length and greater axon surface area 47 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Indeed, clinical studies have established that there is an unclear relationship between radiological signs of LDH and degree of sciatica or other clinical symptoms 15 . In keeping with the main indication for LDHsurg 13 20 ; the neuropathic and painful symptoms of sciatica, we find of interest that height is inversely correlated with peripheral nerve conduction velocity 42 and has been shown to increase risk of peripheral sensory neuropathy in diabetes 43 , peripheral insensate neuropathy 44 , HIV neuropathy 45 and post-mastectomy neuropathic pain syndrome 46 . While the pathogenesis behind the relationship between height and neuropathic pain is unclear, increased height in humans is known to associate with increased axonal length and greater axon surface area 47 .…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, about a third of symptomatic LDH resolve within weeks or months regardless of intervention 13 16 17 with only a fraction (5–10%) leading to persistent sciatica or radiculopathy requiring surgery 18 19 . Microdiscectomy, a minimally invasive spinal surgery for removal of herniated lumbar disc tissue, is indicated only for individuals with severe, progressive and persistent sciatica symptoms that are consistent with location of the radiologically confirmed herniated disc 13 20 . These surgical criteria, therefore, define a clear and specific phenotype of sciatica secondary to LDH pathology that we here show associates strongly with a sequence variant at 8q24.21 between GSDMC and CCDC26.…”
mentioning
confidence: 99%
“…28,30,32,41,[46][47][48] The recurrence rate in our study was 2.6%, which is lower than the rates reported in the literature (7.1 to 12.7%). [49][50][51][52][53] The rate of residual postoperative complaints in our study population was 71.1%. Residual back pain occurred in 43.3% of cases, which was higher than one study that reported a 17% rate for backache at the time of follow-up.…”
Section: Discussion Outcomementioning
confidence: 99%
“…Operations for lumbar disc herniation are numerous [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] and have been performed since the 1934 publi- cation by Mixter and Barr [ 33 ]. Indeed, operations for lumbar disc herniation are the most frequently done neurosurgical procedures.…”
Section: Introductionmentioning
confidence: 99%